Comparative Study Between Intra Operative Difficulties in the Management of Wilms’ Tumor by SIOP and COG Protocol (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: The survival of Wilms’ tumor patients with favorable histology has improved dramatically in response to the introduction and use of current multimodal therapy. Though the SIOP and COG approaches produce nearly identical clinical outcomes, a valid debate about the relative merits of each approach continues.Objective: To Compare the intra operative difficulties in management of Wilms’ tumor by SIOP and COG protocol. Methods: This cross-sectional observational study was carried out in the Department of Pediatric Surgery in Dhaka Medical College Hospital, Dhaka from January, 2021 to July, 2022 over a period of 19 months to compare the intra operative difficulties in the management of Wilms’ tumor by SIOP and COG protocol. A total of 20 patients with Wilms' tumor scheduled for surgery at the Department of Pediatric Surgery, Dhaka Medical College Hospital, Dhaka and Bangladesh Shishu (Children) Hospital and Institute, Dhaka were enrolled in this study as per selection criteria. Two protocols were compared on the basis of per operative tumor spillage, complete resection, operative time, per operative blood loss, tumor weight and lymph node sampling. Statistical Package of Social Science (SPSS) 23 was used for data analysis.Results: More than half of the children were ≤2.5 years old. Tumor spillage was observed significantly lower in SIOP group (10.0%) than in COG group (70.0%) in this study (p0.05). Regarding tumor stages, stage I and II were 40.0% each and stage III was 20.0% in SIOP group. In COG group, Stage I, stage II and stage III were 20.0%, 10.0% and 70.0% respectively (p>0.05). Lymph node sampling could be done in 80.0% cases in SIOP group and 50.0% cases in COG group (p>0.05). Median operative time was 80 min in SIOP group and 120 min in COG group but the difference was not statistically significant (p>0.05). Blood loss was smaller in SIOP group (median: 60 ml) than COG group (median: 65 ml), but the difference was not statistically significant (p>0.05). Tumor weight was lighter in SIOP group (median: 550gm) than COG group (median: 675gm) (p>0.05).Conclusion: According to this study findings, SIOP protocol showed less operative difficulties than COG protocol in the management of Wilms' tumor.Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 44-48